Analisis Manfaat Pengadaan Barang dan Jasa Dengan Menggunakan Metode E-Procurement - Faza rahmania; Siti sa’adah khoeriyah; Syakiro rais; Sigit djalu purwoko (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Procurement is one of the results of the use of internet-based information technology in efforts to carry out the process of procuring goods and services starting from the source search process, negotiation, ordering, receiving, to re-inspection after purchase both separately and simultaneously. so that it is more integrated, effective and efficient. This research was conducted with the aim of seeing, studying, finding out what benefits are obtained from the results of internet-based information technology, namely E-Procurement, in the procurement process. This research uses qualitative methods with literature study or research review data collection techniques, namely reviewing and re-analyzing previous scientific research related to the benefits of using e-procurement. The results of this research are that e-procurement has many benefits and is better than conventional procurement which can be used as an indicator for assessing the performance of E-Procurement which has the benefits of being effective, efficient, transparent, accountable and can support the smooth process of procuring goods and services. monitoring process.